Sistematika Mushaf Al-Qur’an - Ismail, Ismail (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2018)
The role of friends is very important in the writing of the Qur'an, especially the Khulafaur Rosyidin, from the Caliph Abu Bakr who collected the writing of the Qur'an on the proposal of Umar's friend, and during the Kholifah Uthman ibn Affan united the Mushaf into a single reference ie Ottoman manuscripts then multiplied and shipped to all corners of the world. The systematic laying of verses and letters is not in accordance with the cause of the decline of the verse. And we all know if the Qur'an is collected as a Mushaf, while the above factors are still lingering, then the Manuscripts that have been collected are clearly going to change and deviate. The role of friends is very important in the writing of the Qur'an, especially the Khulafaur Rosyidin, from the Caliph Abu Bakr who collected the writing of the Qur'an on the proposal of Umar's friend, and during the Kholifah Uthman ibn Affan united the Mushaf into a single reference ie Ottoman manuscripts then multiplied and shipped to all corners of the world